How Green Mindful Leadership Drives Employee Green Creativity: The Role of Employee Resilience, Green Identity, and Workplace Digitalization - Huang Mei-jiao (SAGE Open)
The green intentions of leaders are crucial for stimulating employees’ green creativity, but there is a dearth of research on how green mindful leadership affects employee green creativity, including the pathways and boundary conditions. This study applies social cognitive theory, role identity theory, and conservation of resources theory to construct a chained mediation model where green mindful leadership influences employee green creativity through employee resilience and green role identity, and also investigates the moderating effect of workplace digitalization. A survey of 305 employees from green digital enterprises was conducted, and the theoretical model was tested using SPSS (a statistical software package widely used for data analysis) and Bootstrap methods (a resampling technique used to estimate statistics on a population by sampling a dataset with replacement). The findings reveal that: (1) green mindful leadership positively affects employee green creativity; (2) employee resilience and green role identity partially mediate the impact of green mindful leadership on employee green creativity; (3) employee resilience enhances green role identity, and these two factors act as a sequential mediator in the relationship between green mindful leadership and employee green creativity; (4) The positive influence of workplace digitalization on employee green creativity through the enhancement of green role identity not only serves as a moderating role for the mediating effect of green role identity but also acts as a moderator in the chain mediation relationship. In light of the research findings, recommendations are offered on how to improve employee green creativity to help enterprises respond to environmental pressures and achieve innovative development.